2014
DOI: 10.3389/fpsyg.2014.01447
|View full text |Cite
|
Sign up to set email alerts
|

Long term impact of emotional, social and cognitive intelligence competencies and GMAT on career and life satisfaction and career success

Abstract: Career scholars have called for a broader definition of career success by inviting greater exploration of its antecedents. While success in various jobs has been predicted by intelligence and in other studies by competencies, especially in management, long term impact of having intelligence and using competencies has not been examined. Even in collegiate outcome studies, few have examined the longer term impact on graduates' careers or lives. This study assesses the impact of demonstrated emotional, social, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 52 publications
(72 reference statements)
4
69
0
Order By: Relevance
“…These studies have indicated that EI is associated with a higher degree of life Positive aging: the relationship between emotional intelligence and psychological, social and physical wellbeing Volume 3 Issue 1 -2018 Galdona N, 1 Martínez-Taboada C, 2 Etxeberria I,3 Urdaneta E, 4 Aldaz E satisfaction. [16][17][18]8,12 In line with those studies Galdona 12 found a relevant finding between perceived EI and life satisfaction. Perceived EI is the ability to pay attention to emotions, to understand and regulate them.…”
Section: Emotional Intelligence and Psychological Functioningsupporting
confidence: 77%
“…These studies have indicated that EI is associated with a higher degree of life Positive aging: the relationship between emotional intelligence and psychological, social and physical wellbeing Volume 3 Issue 1 -2018 Galdona N, 1 Martínez-Taboada C, 2 Etxeberria I,3 Urdaneta E, 4 Aldaz E satisfaction. [16][17][18]8,12 In line with those studies Galdona 12 found a relevant finding between perceived EI and life satisfaction. Perceived EI is the ability to pay attention to emotions, to understand and regulate them.…”
Section: Emotional Intelligence and Psychological Functioningsupporting
confidence: 77%
“…Green positive guidance endeavors to provide support to individuals regarding the construction of their own futures in line with their aims and authentic selves (Di Fabio, 2014c), the expression of their own talents and potential, the enhancement of positive relationships with significant others, and building individual strengths (Boyatzis et al, 2002, 2015; Boyatzis and Saatcioglu, 2008; Di Fabio and Palazzeschi, 2008a,b, 2009, 2012; Di Fabio and Blustein, 2010; Di Fabio and Kenny, 2012a,b; Di Fabio et al, 2012, 2013; Amdurer et al, 2014; Di Fabio, 2014b, 2015a; Di Fabio and Saklofske, 2014a,b; Kenny et al, 2014; Di Fabio, 2015b). At the same time, green positive guidance endeavors to respond to environmental concerns, fairness institutions, social justice, the environment, and the exploitation of resources (Guichard and Di Fabio, 2015; Di Fabio, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, longitudinal studies have established that adults can develop ESI competencies shown to predict management, leadership, and professional readiness and effectiveness, and this development sustains far longer than other forms of education or development (Boyatzis, Lingham, & Passarelli, 2010;Boyatzis & Saatcioglu, 2008;Boyatzis, Stubbs, & Taylor, 2002). These same competencies have been shown to predict life and career satisfaction as well as career success 5-19 years later (Amdurer et al, 2014). Thus, leadership competency development programs using ICT and ELT pedagogies hold significant promise for enhancing career readiness and success.…”
Section: An Approach To Developing Competencies That Promote Career Rmentioning
confidence: 90%
“…A different longitudinal study on the long-term impact of ESI competency development on career satisfaction and success in cohorts from the same MBA program 5-19 years after graduation found that emotional, social, and cognitive competencies assessed at graduation predicted subsequent career satisfaction and success (Amdurer et al, 2014)-again showing that ESI leadership competencies can be developed and learned.…”
Section: A Course On Leadership Assessment and Development (Lead) Usingmentioning
confidence: 99%